AKSARA BALI DALAM PENULISAN NAMA ORANG - Putu Reland Dafincy Tangkas; Made Reland Udayana Tangkas (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2021)
The Balinese script, which is a big tradition of the Balinese language, provides a unique and extraordinary attraction for Balinese cultural life. It should be proud that the Balinese language is one of the local languages of 668 local languages in Indonesia and only a small part has a script system. The existence of Balinese script is increasingly guaranteed by the policy of the Bali Provincial Government which issued Pergub Number 80 of 2018 which protects the use of Balinese language, script, and literature as well as the implementation of the Balinese Language Month every February. This resulted in the Balinese script being able to enter the wider public realm.All public information should be followed by writing Balinese script, whether it is government agencies, private sector, customary domains, holy places, business entities, and individual information. Individual information that is often used is the name. Thus, the name is important to be copied into Balinese script. The ability to write names using Balinese script basically needs to be mastered by every Balinese. Because, from elementary school to high school, the basics of Balinese script must have been given, especially about writing names. The ability to write names into Balinese script is also a form of public concern for the existence of Balinese script in the midst of life. Although some people are able to write their names into Balinese script, it turns out that there is still confusion and ambiguity that arises so that it becomes an obstacle to the community's ability. The confusion also arises due to the view of the freedom of writing individually which is felt to add to the ambiguity.In order to be able to write names into Balinese script correctly, there are several things that should be noted so that there is no confusion and error considering that Balinese script itself also has different rules from Latin letters. First, syllable decapitation is a serious concern because Balinese script adheres to a syllabic system. Second, the pronunciation must also be considered because the writing of the Balinese script is adjusted to the pronunciation. And thirdly, pay attention to the use of swalalita script and the rules of pairs of pageh in names derived from Old Javanese/Kawi or Sanskrit. These three things are still a problem when someone wants to copy a name into Balinese script. By paying attention to these three things, it is hoped that the confusion of writing the name will not occur.Keywords ; People's Name, Balinese Script